Temporal Trends of Intravenous Thrombolysis Utilization in Acute Ischemic Stroke in a Prospective Cohort From 1998 to 2019: Modeling Based on Joinpoint Regression - Olavarría, Verónica V.; Hoffmeister, Lorena; Vidal, Carolina; Brunser, Alejandro M.; Hoppe, Arnold; Lavados, Pablo M. (Frontiers in Neurology, 2022)
Introduction: The frequency of Intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) is lower than it should be in several regions of the world. It is unclear what interventions can produce significant improvements in IVT utilization. We aimed to investigate the temporal trends in IVT in AIS and identify changes in time that could be associated with specific interventions. Methods: We included AIS patients admitted from January 1998 to December 2019 to our Institution. To analyze trends in utilization and time points in which they changed, we performed a Joinpoint regression analysis. Interventions were assigned to a specific category according to the Behavior Change Wheel framework intervention function criteria. Results: A total of 3,361 patients with AIS were admitted, and 538 (16%) received IVT. There were 245 (45.5%) women, and the mean age and median National Institutes of Health Stroke Scale scores were 68.5 (17.2) years and 8 (interquartile range, 4–15), respectively. Thrombolysis use significantly increased by an average annual 7.6% (95% confidence interval, 5.1–10.2), with one Joinpoint in 2007. The annual percent changes were 0.45% from 1998 to 2007 and 9.57% from 2007 to 2019, concurring with the stroke code organization, the definition of door-to-needle times, and the extension of the therapeutic window. Conclusions: The IVT rates consistently increased due to a continuous process of protocol changes and multiple interventions. The implementation of a complex multidisciplinary intervention and the definition of a hospital quality control metric were associated with a significant change in this trend.